Physical Disability and Psychedelic Therapies: An Agenda for Inclusive Research and Practice - Mintz, Kevin T.; Gammer, Brinn; Khan, Amanda J.; Shaub, Gretchen; Levine, Steven; Sisti, Dominic (Frontiers in Psychiatry, 2022)
Over the past decade, there has been an increase in the number of clinical trials for psychedelic therapies as treatments for a wide range of psychiatric conditions. We are concerned that research organizations overseeing these trials have neglected the inclusion of individuals with physical and sensory disabilities. We suggest that psychedelic research organizations should prioritize and plan for the inclusion of individuals with physical and sensory disabilities to address the mental health burdens they confront. Not doing so risks reinforcing structural ableism in healthcare: the discriminatory manifestation of lowered expectations towards people with disabilities on the part of medical providers. Drawing on scholarship from disability studies and medical ethics, we offer four recommendations for disability inclusion in research. We recognize particular populations shoulder significant mental health burdens; these populations deserve priority and should be given a range of accommodations. We emphasize the need for extensive disability awareness training for those facilitating psychedelic therapies and encourage psychedelic researchers and therapists to exercise cultural humility towards individuals with physical and sensory disabilities. This article should be the impetus for further scholarship and debate about how psychedelic research and therapies can be made accessible to members of disability communities who might benefit.